PARALLEL FORMATION AND SYNERGISM OF HYDROLYTIC ENZYMES AND PEPTAIBOL ANTIBIOTICS, MOLECULAR MECHANISMS INVOLVED IN THE ANTAGONISTIC ACTION OF TRICHODERMA-HARZIANUM AGAINST PHYTOPATHOGENIC FUNGI - SCHIRMBOCK, M; LORITO, M; WANG, YL; HAYES, CK; ARISANATAC, I; SCALA, F; HARMAN, GE; KUBICEK, CP (AMER SOC MICROBIOLOGY, 1994)
Chitinase, beta-1,3-glucanase, and protease activities were formed when Trichoderma harzianum mycelia, grown on glucose as the sole carbon source, were transferred to fresh medium containing cell walls of Botrytis cinerea. Chitobiohydrolase, endochitinase, and beta-1,3-glucanase activities were immunologically detected in culture supernatants by Western blotting (immunoblotting), and the first two were quantified by enzyme-linked immunosorbent assay. Under the same conditions, exogenously added [U-C-14]valine was incorporated in acetone-soluble compounds with an apparent M(r) of <2,000. These compounds comigrated with the peptaibols trichorzianines A(1) and B-1 in thin-layer chromatography and released [U-C-14]valine after incubation in 6 N HCl. Incorporation of radioactive valine into this material was stimulated by the exogenous supply of alpha-aminoisobutyric acid, a rare amino acid which is a major constituent of peptaibols. The obtained culture supernatants inhibited spore germination as well as hyphal elongation of B. cinerea. Culture supernatants from mycelia placed in fresh medium without cell walls of B. cinerea did not show hydrolase activities, incorporation of [U-C-14]valine into peptaibol-like compounds, and inhibition of fungal growth. Purified trichorzianines A(1) and B-1 as well as purified chitobiohydrolase, endochitinase, or beta-1,3-glucanase inhibited spore germination and hyphal elongation, but at concentrations higher than those observed in the culture supernatants. However, when the enzymes and the peptaibols were tested together, an antifungal synergistic interaction was observed and the 50% effective dose values obtained were in the range of those determined in the culture supernatants. Therefore, the parallel formation and synergism of hydrolytic enzymes and antibiotics may have an important role in the antagonistic action of T. harzianum against fungal phytopathogens.
Keywords: VOLATILE ANTIBIOTICS; CHITINOLYTIC ENZYMES; ANTIFUNGAL ACTIVITY; TRICHORZIANINE-A; MODEL MEMBRANES; SPECIES-GROUPS; REESEI; ENDOCHITINASE; PROTEIN; CHITOBIOSIDASE; Biotechnology & Applied Microbiology; Microbiology